Dynamics Performance of Native Chicken Agribusiness in Indonesia - Broto Wibowo (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2016)
Native chicken can be found in almost every region of Indonesia. There are three systems of raising native chicken, i.e. extensive, semi-intensive and intensive. Raising native chicken under intensive system could enhance productivity and revenue. The prospect of raising native chicken has a potential market with a nieche segmented consumer. Native chicken business for meat and egg production is feasible to provide economic benefit for stakeholders, such as farmers, traders, wholesaler and retailers. Institutional empowerment towards cooperative with simultaneous upstream through downstream agribusinesses could increase farmers’ income. This could be applied by individual business or cooperative to attain higher efficiency of production system. Government support as farmers’ motivator and supervision is needed to achieve the success of native chicken business that improves farmers’ welfare.